Mathematical skills of the nursing and midwifery students of Sakarya University school of healht sciences - Nursan Çinar; Aysegül Dogan (Universidade Federal de Goias, 2006)
This study was carried out with the purpose of determining the Nursing and Midwifery students' interest and skills in mathematics, and their skills in calculating the medication dosages. In the study, a survey form comprising 16 questions having the purpose of determining the students' demographical characteristics and interest in mathematics, and the Medication Skill Test (MCS Test), which had been also prepared by the researchers, were used. The Medication Skill Test (MCS Test) were developed, by the researchers, by means of reviewing the relevant literature, particularly the studies carried out by Grandell-Neime et al. and the pharmacology test books. The MCS Test consisted of 25 questions, of which eleven were about general mathematics and fourteen were about the calculation of the medication dosages. The answers the students gave to the questions were evaluated as correct or incorrect. The sampling of the research comprised totally 73 students from the 2nd, 3rd and 4th grades of the midwifery classes, and totally 142 students from the 1st, 2nd, 3rd and 4th grades of the nursing classes. The survey form were applied to the students by providing the examination conditions and giving 20 minutes time. The data collected was evaluated in computer. It was determined that 96.5 % of the nursing students (n: 137) and 90.4 % of the midwifery students (n: 66) liked the mathematics. 90.1 % of the nursing students (n: 128) and 83.6 % of the midwifery students (n: 61) stated that they found mathematics enjoyable, and likewise, 35.2 % of the nursing students (n: 50) and 34.2 % of the midwifery students (n: 25) stated that they deemed the mathematics as necessary in nursing. 66.9 % of the nursing students (n: 95) and 63.0 % of the midwifery students (n: 46) stated that they had good mathematical skills. 60.6 % of the nursing students (n: 86) and 75.3 % of the midwifery students (n: 55) stated that they didn't deem themselves as adequate in calculating the medication dosages. 65.5 % of the nursing students (n: 93) and 74.0 % of the midwifery students (n: 54) stated that they experienced occasional problems in the mathematical calculations relating to the medication administrations. According to the MCS Test results, it was seen that the lowest correct answering rate was 26.9 % for the nursing students and 5.5 % for the midwifery students, while the highest correct answering rate was 98.6 % for the nursing students and 94.5 % for the midwifery students. Medication administration is an essential skill for nurses and midwives. Any mistake in calculation can lead to medication error and life threatening situations for patients. In the study, it was found that the mathematical skills of the nursing and midwifery students were weak and they didn't feel adequate in the calculation of the medication dosages. Determining and overcoming this inadequacy of the students during their education would prevent the problems they possibly face in their profession after their graduation.